Inoculation of tomato plants with rhizobacteria suppresses development of whitefly Bemisia tabaci (GENNADIUS) (HEMIPTERA: ALEYRODIDAE): Agro-ecological application. - Redouan Qessaoui (PLoS ONE, 2020)
In agroecosystems, soil biodiversity is increasingly becoming more recognized as providing benefits to both plants and human health. It performs a wide variety of ecological services beyond the recycling of nutrients to plant growth and manage pests and diseases below the economic injury level. This study investigated the effects of three Pseudomonas isolates (Q172B, Q110B and Q036B), isolated from untreated tomato rhizospheric soil, as a biological control agent of Bemisia tabaci which is a key pest of tomato crops. The study was conducted under laboratory and glasshouse conditions and the water treatment was used as a control. Adult mortality rates were assessed during three days at 24h interval and larva mortality rates were evaluated during six days after treatment at 48h interval. Results indicate that Q036B isolate has a faster effect on B. tabaci adult and larvae. Under laboratory conditions, all three Pseudomonas isolates (Q110B, Q036B and Q172B) have a significant effect on B. tabaci adult mortality compared to control. The earliest and the most important mortality rate of 76% was recorded by Q036B. Two isolates Q036B and Q110B caused a significant mortality on B. tabaci larvae; with highest mortality effect (79%) was observed for Q036B compared to control. However, Q172B has no mortality effects on B. tabaci larvae under laboratory conditions. In glasshouse conditions, only Q036B provided high mortality rates of 91% at 168h after treatment. The results of this study indicate that the Pseudomonas isolate Q036B significantly suppresses B. tabaci in tomato plant and could substitute the excessive use of chemicals. Current research indicates that soil biodiversity could be promising to preserve agro-ecological sustainability.